Analisis Strategi Pemasaran Berkonsep Low Cost Carrier (LCC) Untuk Meningkatkan Daya Saing Dengan Pendekatan Analisis Swot (Studi Pada Maskapai Penerbangan di PT.Lion Air) - Wulandari Fadia Agustin (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the marketing strategy carried out by the Lion Air airline with the concept of Low Cost Carrier and to know the SWOT analysis of the marketing strategy to increase the competitiveness of Lion Air. This study uses qualitative methods, data collection with documentation, observation and interview techniques. Source of data comes from primary data through interviews with managers of Pt. Lion Air, while secondary data was extracted from the internet site. The results of the strategy used by Lion Air airline with the Low Cost Carrier concept have been going well and become an attraction for consumers, then SWOT analysis on Lion Air airline using the company's strengths and opportunities can facing or avoiding the weaknesses and threats of other companies. So it can be concluded that Lion Air has great strengths and opportunities.